Second Language Accent Faking Ability Depends on Musical Abilities, Not on Working Memory - Coumel, Marion; Christiner, Markus; Reiterer, Susanne Maria (Frontiers in Psychology, 2019)
Studies involving direct language imitation tasks have shown that pronunciation ability is related to musical competence and working memory capacities. However, this type of task may measure individual differences in many different linguistic dimensions, other than just phonetic ones. The present study uses an indirect imitation task by asking participants to a fake a foreign accent in order to specifically target individual differences in phonetic abilities. Its aim is to investigate whether musical expertise and working memory capacities relate to phonological awareness (i.e., participants’ implicit knowledge about the phonological system of the target language and its structural properties at the segmental, suprasegmental and phonotactic levels) as measured on this task. To this end, French native listeners (N = 36) graded how well German native imitators (N = 25) faked a French accent while speaking in German. The imitators also performed a musicality test, a self-assessment of their singing abilities and working memory tasks. The results indicate that the ability to fake a French accent correlates with singing ability and musical perceptual abilities, but not with working memory capacities. This suggests that heightened musical abilities may lead to an increased phonological awareness probably by providing participants with highly efficient memorization strategies and highly accurate long-term phonetic representations of foreign sounds. Comparison with data of previous studies shows that working memory could be implicated in the pronunciation learning process which direct imitation tasks target, whereas musical expertise influences both storing of knowledge and later retrieval here assessed via an indirect imitation task.